SOURCE POTENTIAL OF THE MESOZOIC-CENOZOIC ROCKS IN THE SOUTH CASPIAN BASIN AND THEIR ROLE IN FORMING THE OIL ACCUMULATIONS IN THE LOWER PLIOCENE RESERVOIRS - Feyzullayev A.A.; Guliyev I.S.; Tagiyev M.F. (My University, 2001)
The source potential and organic maturity of the shales alternating with the reservoir beds in the Lower Pliocene Productive Series - the major oil-bearing unit in the South Caspian Basin - are inadequate to have formed the observed petroleum accumulations. A geochemical study of rocks collected from wells and outcrop localities has been carried out to assess the oil- and gas-generative properties of the Middle Jurassic to Lower Pliocene sediments of the basin. On the whole the section under review is characterized by poor to good organic richness and low hydrogen index, suggesting type 2 and 3 kerogens. Organic-rich sediments are relatively frequent in parts of the Oligocene-Miocene interval. Source-to-oil correlation based on carbon isotope signatures points to a largely epigenetic origin for the oils reservoired in the Lower Pliocene. Isotopically, the oils in these Productive Series reservoirs are best correlated with organic matter contained in the Miocene sediments.
Keywords: Cenozoic; Mesozoic; Pliocene; Source potential; South Caspian Basin; oil accumulations; Mesozoic; Мезозой; Cenozoic; Cenozoic::Neogene::Pliocene; Кайнозой; Кайнозой::Неоген::Плиоцен